A magnetic field assisted in-situ nanocrystalline thermal spray coating and a method of making the same

CN122918486APending Publication Date: 2026-10-16HANGFA EXCELLENT MATERIALS (ZHENJIANG) ADDITIVE MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611248650.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

现有常规超音速火焰喷涂涂层依靠熔融颗粒逐层堆叠沉积成型,存在多项固有结构缺陷:熔滴高速撞击基材后发生急速非平衡凝固,晶粒沿散热方向择优生长形成粗大柱状晶,晶界疏松、结合薄弱,腐蚀介质易沿晶界向内渗透诱发基材腐蚀;涂层呈现典型片层堆叠结构,层间存在大量间隙、扁平孔隙与弱结合界面,在热循环、交变冲击工况下极易发生层间滑移、开裂与整片剥落,是制约涂层服役寿命的关键短板

Benefits of technology

采用原位生成纳米晶的制备思路,无需额外掺入纳米粉体,依靠熔融熔滴在定向稳恒磁场约束下凝固,配合La2O3-ZrB2复合形核助剂协同诱导,即可在凝固过程中原位析出尺寸50~200nm的弥散分布纳米晶,规避了纳米粉体烧损、团聚和送粉困难等问题;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918486A_ABST
    Figure CN122918486A_ABST
Patent Text Reader

Abstract

The present application relates to the field of material surface strengthening and thermal spraying technology, and particularly relates to a magnetic field assisted in-situ nanocrystalline thermal spraying coating and a preparation method thereof, the present application takes Cr3C2 and NiCrBSi nickel-based self-fluxing alloy powder as a matrix, and compounding La2O3-ZrB2 composite nucleation agent, without additional doping of nano-powder, adopting the whole process coupling process of substrate magnetic field pre-polarization, spraying whole process steady magnetic field assisted high velocity oxygen fuel deposition, and magnetic field assisted low temperature aging, inhibiting the growth of coarse columnar crystal of molten droplet, inducing in-situ generation of 50-200nm dispersed nanocrystal, constructing micron-nanometer double scale dense texture and eliminating the traditional layered weak interface, and regulating the residual tensile stress of the coating to a uniform compressive stress field; the prepared coating has a porosity of less than or equal to 1.9%, an interface bonding strength of greater than or equal to 65MPa, a hot shock cycle life at 800 DEG C water cooling of more than 3 times that of a conventional coating, a high temperature friction and wear rate reduction of more than 70%, and is suitable for surface protection of high temperature wear-resistant and corrosion-resistant components in metallurgy, thermal power, petrochemical and mining fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of material surface strengthening and thermal spraying technology, specifically a magnetic field-assisted in-situ nanocrystalline thermal spray coating and its preparation method. Background Technology

[0002] Thermal spraying is a mainstream technology for improving the wear resistance, corrosion resistance, and high-temperature resistance of component surfaces. Among these technologies, supersonic flame spraying is the most widely used in the field of hard wear-resistant coatings due to its high particle velocity and low oxidation level. Existing conventional supersonic flame spraying coatings rely on the deposition of molten particles layer by layer, which has several inherent structural defects: after the molten droplets impact the substrate at high speed, rapid non-equilibrium solidification occurs, and grains preferentially grow along the heat dissipation direction to form coarse columnar crystals. The grain boundaries are loose and the bonding is weak, making it easy for corrosive media to penetrate inward along the grain boundaries and induce substrate corrosion. The coating exhibits a typical lamellar stacked structure with a large number of gaps, flat pores, and weak bonding interfaces between layers. Under thermal cycling and alternating impact conditions, interlayer slippage, cracking, and peeling of entire sheets can easily occur, which are key shortcomings that restrict the service life of the coating.

[0003] Meanwhile, the rapid solidification process of molten droplets generates large-scale, uneven residual tensile stress within the coating. Microcracks continuously emerge and propagate at stress concentration points. Current industry improvements are largely limited to adjusting powder ratios, optimizing spraying parameters, adding multiple transition layers, post-spray sealing, or local remelting. These methods only slightly reduce coating porosity and cannot suppress columnar crystal growth, eliminate layered weak interfaces, or directionally regulate internal stress at the solidification mechanism level. Furthermore, existing nano-modified spraying methods often employ physical mixing of nanoparticles, which suffer from severe high-temperature oxidation and burn-off of nanoparticles, powder agglomeration leading to nozzle clogging, unstable powder feeding, low deposition efficiency, and poor stability in large-scale production. The problem of thermal shock peeling has long remained unresolved in the industry. Therefore, there is an urgent need to develop a magnetic field-assisted in-situ nanocrystalline thermal spray coating and its preparation method to overcome the shortcomings in current practical applications. Summary of the Invention

[0004] The purpose of this invention is to provide a magnetic field-assisted in-situ nanocrystalline thermal spray coating and its preparation method, so as to solve the problems mentioned in the background art.

[0005] To achieve the above objectives, the present invention provides the following technical solution: A magnetic field-assisted in-situ nanocrystalline thermal spray coating is attached to the surface of a metal substrate and comprises a Cr3C2 hard phase and a NiCrBSi nickel-based self-fluxing alloy binder phase. The coating has no lamellar weak bonding interface inside, and is composed of a micron-scale dense texture consisting of a micron-scale hard matrix phase and in-situ self-generated nanocrystals. The in-situ self-generated nanocrystals are dispersed at the grain boundaries and micro-interstic spaces of micron-sized particles; The coating has no through-holes or continuously expanding microcracks, and the overall internal stress is in a state of uniform residual compressive stress distribution.

[0006] As a further aspect of the present invention, the size of the in-situ self-generated nanocrystals is 50–200 nm.

[0007] As a further aspect of the present invention: the composition of the composite spraying powder for preparing the coating, by mass percentage, is: Cr3C2 35%–45%, NiCrBSi nickel-based self-fluxing alloy powder 52%–62%, La2O3 1.0%–2.0%, and ZrB2 1.0%–2.0%.

[0008] A method for preparing the above-described magnetic field-assisted in-situ nanocrystalline thermal spray coating includes substrate pretreatment, powder pretreatment, and supersonic flame spraying steps, and further includes: The substrate is pre-polarized by magnetic field before spraying; A constant magnetic field is continuously applied throughout the spraying process to assist deposition. After spraying, the coating is subjected to low-temperature aging and setting treatment in a stable magnetic field atmosphere; The powder used for spraying is a composite spraying powder containing Cr3C2, NiCrBSi nickel-based self-fluxing alloy powder, La2O3 and ZrB2.

[0009] As a further aspect of the present invention: the magnetic field direction of the magnetic field pre-polarization treatment is perpendicular to the substrate surface, the magnetic field strength is 15-35 mT, and the treatment time is 10-20 min; During the supersonic flame spraying process, the direction of the steady magnetic field is perpendicular to the surface of the substrate, and the magnetic field strength is maintained at 15-35 mT. The magnetic field strength of the low-temperature aging and shaping treatment is 15–35 mT.

[0010] As a further aspect of the present invention: the substrate pretreatment includes a sandblasting roughening process: Using 80-100 mesh white corundum abrasive, the sandblasting pressure is controlled at 0.4-0.6 MPa, the sandblasting angle is controlled at 70°-80°, and the surface roughness Ra of the substrate after treatment is 4.0-6.0 μm.

[0011] As a further aspect of the present invention: the process parameters for the supersonic flame spraying include: Oxygen flow rate 45m 3 / h, kerosene flow rate 22L / h, powder feeding rate 55g / min, spraying distance 300mm, spray gun moving speed 600mm / s.

[0012] As a further aspect of the present invention: the low-temperature aging and shaping treatment is carried out under inert nitrogen protection, the heating rate is controlled at 3-5℃ / min, the temperature is raised to 400℃ and then kept at a constant temperature for 60min, and the furnace is cooled after the holding period is over.

[0013] As a further aspect of the present invention: after the low-temperature aging and shaping treatment is completed, the workpiece cooled to room temperature is left to stand for 24 hours for room temperature natural aging to obtain the final coating product.

[0014] Compared with the prior art, the beneficial effects of the present invention are: The preparation method adopts the in-situ generation of nanocrystals, which does not require the addition of nanopowder. It relies on the solidification of molten droplets under the confinement of a directional and constant magnetic field. With the synergistic induction of La2O3-ZrB2 composite nucleation aid, nanocrystals with a size of 50-200 nm can be precipitated in situ during the solidification process, avoiding problems such as nanopowder burn-off, agglomeration and difficulty in powder delivery. It can eliminate the inherent weak bonding interface of layered stacking in traditional thermal spraying, and change the orientation of droplet solidification and growth through magnetic field, so that the coating structure is continuous without traditional lamellar boundaries, eliminating the failure mode of interlayer peeling from the structural root and improving the coating's anti-peeling ability. It can directionally control the residual stress of the coating, and transform the concentrated residual tensile stress inside the coating into a uniformly distributed residual compressive stress field by controlling the solidification stress and subsequent aging reconstruction through magnetic field, thereby inhibiting the initiation and propagation of microcracks. The 800℃ water-cooled thermal shock cycle life is more than 3 times that of conventional coatings. A dense texture at both the micron and nanoscales is constructed. The micron-sized Cr3C2 hard phase provides a wear-resistant skeleton, and the in-situ nanocrystalline seal blocks grain boundaries and micropores. The overall porosity of the coating is ≤1.9%, and the interfacial bonding strength is ≥65MPa. This effectively blocks the penetration of corrosive media and reduces the high-temperature friction and wear rate by more than 70%, thus synergistically improving the wear resistance and corrosion resistance of the coating. The process is simple to support, requires low magnetic field strength and low energy consumption, and can be adapted to various base materials such as carbon steel, alloy steel and cast steel. It is suitable for mass production of protective components for high temperature-wear-corrosion coupled working conditions in multiple industries. Attached Figure Description

[0015] Figure 1 This is a microstructure diagram of the coating in Example 1 of the present invention.

[0016] Figure 2 This is a microstructure diagram of the coating in Example 2 of the present invention.

[0017] Figure 3 This is a microstructure diagram of the coating in Example 3 of the present invention.

[0018] Figure 4 This is a microstructure diagram of the coating in Example 4 of the present invention.

[0019] Figure 5 This is a microstructure diagram of the coating in Example 5 of the present invention.

[0020] Figure 6 This is a microstructure image of a conventional thermal spray coating for comparison. Detailed Implementation

[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] The specific implementation of the present invention will be described in detail below with reference to specific embodiments.

[0023] Please see Figures 1-6 This invention provides a magnetic field-assisted in-situ nanocrystalline thermal spray coating. The coating is attached to the surface of a metal substrate and has no weak bonding interface like the sheet-like structure of traditional thermal spray coatings. Instead, it consists of a micron-scale hard matrix phase and in-situ self-generated nanocrystals to form a dense texture at both the micron and nanoscale levels. The size of the in-situ self-generated nanocrystals is controlled between 50 and 200 nm and they are uniformly filled in the grain boundaries and micro-gap of micron particles. The coating has no through-pores or continuously expanding microcracks. The overall internal stress distribution of the coating is mainly uniform residual compressive stress.

[0024] The composite spraying powder used to prepare the above coating has the following composition by mass percentage: Cr3C2 35%–45%, NiCrBSi nickel-based self-fluxing alloy powder 52%–62%, La2O3 1.0%–2.0%, and ZrB2 1.0%–2.0%. When designing the powder formulation, the strongly magnetic NiCrBSi powder is considered the main component, serving as the binder and the primary target for magnetic stirring. The mixture of Cr3C2, La2O3, and ZrB2 is considered a whole. Cr3C2 acts as a hard phase, providing excellent wear resistance to the coating. La2O3 reduces the surface energy of the molten droplets and increases the nucleation density during solidification. ZrB2 is a high-temperature stable heterogeneous nucleation particle that induces in-situ precipitation of nanocrystals during rapid droplet solidification. The synergistic effect of these two components provides the thermodynamic conditions for the dispersed precipitation of nanocrystals in situ during droplet solidification, achieving nanocrystal modification of the coating without the need for additional nanoparticles. Furthermore, by superimposing a magnetic field, the proportion of NiCrBSi binder is adjusted, and the strength of the molten pool rotation is controlled to change the coating performance.

[0025] The coating preparation method includes six steps: precision pretreatment of the substrate, magnetic field prepolarization of the substrate, powder pretreatment, synchronous magnetic field-assisted supersonic flame spraying, magnetic field-assisted low-temperature aging and shaping, and room temperature natural aging. The specific details are as follows: S1 substrate precision pretreatment The workpiece to be coated is subjected to degreasing, rust removal, mechanical grinding and sandblasting roughening treatment in sequence to control the surface roughness Ra = 4.0~6.0μm. After blowing off the surface dust with clean compressed air, it is dried for later use.

[0026] Specifically, the sandblasting process uses 80-100 mesh white corundum abrasive, with the sandblasting pressure controlled at 0.4-0.6 MPa and the sandblasting angle controlled at 70°-80°. This controlled sandblasting roughening process forms a uniform uneven anchoring structure on the substrate surface, enhancing the mechanical bonding strength between the coating and the substrate, while also providing a clean surface for subsequent magnetic field pre-polarization.

[0027] S2 substrate magnetic field prepolarization The roughened workpiece is placed in a steady magnetic field environment with the magnetic field direction perpendicular to the substrate surface and the field strength controlled at 15-35 mT for pre-polarization treatment for 15 min.

[0028] By pre-polarizing the substrate, the interfacial energy level on the substrate surface can be optimized, the spreading and wetting ability of the first droplet on the substrate surface can be improved, the interfacial bonding effect between the coating and the substrate can be strengthened, and the initial magnetic field orientation basis can be provided for the directional solidification of grains in the subsequent spraying process.

[0029] S3 Powder Pretreatment Weigh each component according to the above mass ratio and mix them evenly to prepare a composite spray powder; place the composite powder in a 100℃ oven to dry for 1 hour to remove the water vapor adsorbed by the powder and avoid water vapor vaporization during the spraying process, which would cause pore defects in the coating.

[0030] The particle size range of the composite spraying powder is preferably 15-53 μm, which is suitable for the powder feeding stability and deposition quality requirements of supersonic flame spraying.

[0031] S4 Synchronous Magnetic Field Assisted Supersonic Flame Spraying During the spraying process, a water-cooled annular excitation coil is fitted on the outside of the spray gun, and the magnetic field lines extend along the central axis of the spray gun to the substrate, with the field strength maintained at 15-35 mT. A water-cooled electromagnet is arranged on the back of the substrate to generate a magnetic field perpendicular to the surface of the substrate, with the field strength maintained at 15-35 mT. The magnetic field passes through the molten pool on the surface of the substrate, and the Lorentz force eddy current stirs the inside of the molten pool. The coating is deposited layer by layer using a supersonic flame spraying process.

[0032] Specific parameters for supersonic flame spraying include: oxygen flow rate 45 m³ / h. 3 / h, kerosene flow rate 22m 3 / h, powder feeding rate 55g / min, spraying distance 300mm, spray gun moving speed 600mm / s.

[0033] During the spraying process, the molten metal droplets are constrained by the Lorentz force of the directional steady magnetic field, which restricts the unidirectional preferential growth of grains along the heat dissipation direction and effectively inhibits the formation of coarse columnar crystals. With the synergistic induction effect of the La2O3-ZrB2 composite nucleation aid in the powder, diffusely distributed nanocrystals with a size of 50-200 nm are generated in situ during the solidification of the droplets, constructing a dual-scale continuous dense texture of "micron hard skeleton + in-situ nanocrystal grain boundary filling", eliminating the inherent layered stacking weak bonding interface of traditional thermal spraying.

[0034] S5 Magnetic Field Assisted Low Temperature Aging and Shaping After the coating is applied, the workpiece is kept in a stable magnetic field atmosphere of 15-35 mT and aged under inert nitrogen protection. The heating rate is controlled at 3-5℃ / min. After heating to 400℃, the workpiece is kept at a constant temperature for 60 min. After the holding period, the workpiece is cooled in the furnace with the magnetic field environment to complete the regularization of the coating structure and reconstruction of the residual stress field.

[0035] Specifically, the flow rate of inert protective nitrogen is 10 L / min.

[0036] Low-temperature aging in a magnetic field atmosphere can gradually relax solidification stress without inducing phase transformation of the coating structure, transforming the concentrated residual tensile stress inside the coating into a uniformly distributed residual compressive stress field, inhibiting the initiation and propagation of microcracks, and further improving the coating's resistance to thermal shock spalling.

[0037] S6 Room Temperature Natural Aging The workpiece, cooled to room temperature, is left to stand for 24 hours to release the instantaneous micro-stress generated during the spraying and aging process, thus obtaining the final composite coating product.

[0038] Example 1: In this example, a magnetic field-assisted in-situ nanocrystalline thermal spray coating was prepared using 45# steel as the substrate. The specific steps are as follows: 1. Substrate pretreatment: The 45# steel workpiece is ultrasonically degreased with acetone for 15 minutes, and then sandblasted with 80-mesh white corundum at a sandblasting pressure of 0.5MPa and a sandblasting angle of 75° to control the surface roughness Ra = 5.0μm. After blowing off the surface dust with clean compressed air, it is dried for later use. 2. Substrate magnetic field pre-polarization: The workpiece is placed in a steady magnetic field perpendicular to the surface of the substrate with a field strength of 15mT and pre-polarized for 15min. 3. Powder pretreatment: Prepare composite powder according to the following mass percentages: Cr3C2 35%, NiCrBSi nickel-based self-fluxing alloy powder 62%, La2O3 1.5%, ZrB2 1.5%, mix evenly and dry in an oven at 110℃ for 60 min to remove adsorbed moisture. 4. Synchronous magnetic field-assisted supersonic flame spraying: A magnetic field perpendicular to the substrate surface is applied throughout the spraying process, with the field strength maintained at 15 mT; the supersonic flame spraying process parameters are: oxygen flow rate 45 m³ / h. 3 / h, kerosene flow rate 22L / h, powder feeding rate 55g / min, spraying distance 300mm, spray gun moving speed 600mm / s; 5. Magnetic field-assisted low-temperature aging and setting: Place the workpiece in a 15mT constant magnetic field atmosphere, and introduce nitrogen for protection at a flow rate of 10L / min; heat to 400℃ at a heating rate of 3-5℃ / min, hold at that temperature for 60min, and then cool with the furnace after the holding period. 6. Natural aging at room temperature: After the workpiece cools to room temperature, it is left to stand for 24 hours to obtain the finished coating.

[0039] Performance testing showed that the coating obtained in this embodiment had an interfacial bonding strength of 65 MPa and a porosity of 1.9%. After 42 cycles of water quenching and thermal shock testing at 800℃, the coating failed, and the interlayer oxides within the coating disappeared. The high-temperature friction and wear rate at 800℃ was 1.44 × 10⁻⁶. -5 mm 3 / (N・m).

[0040] Example 2: In this example, a magnetic field-assisted in-situ nanocrystalline thermal spray coating was prepared using 45# steel as the substrate. The specific steps are as follows: 1. Substrate pretreatment: The 45# steel workpiece is ultrasonically degreased with acetone for 15 minutes, and then sandblasted with 80-mesh white corundum at a sandblasting pressure of 0.5MPa and a sandblasting angle of 75° to control the surface roughness Ra = 5.0μm. After blowing off the surface dust with clean compressed air, it is dried for later use. 2. Substrate magnetic field pre-polarization: The workpiece is placed in a steady magnetic field perpendicular to the surface of the substrate with a field strength of 25mT and pre-polarized for 15min. 3. Powder pretreatment: Prepare composite powder according to the following mass percentages: Cr3C2 45%, NiCrBSi nickel-based self-fluxing alloy powder 52%, La2O3 1.5%, ZrB2 1.5%, mix evenly and dry in an oven at 100℃ for 60 min to remove adsorbed moisture. 4. Synchronous magnetic field-assisted supersonic flame spraying: A magnetic field perpendicular to the substrate surface is applied throughout the spraying process, with the field strength maintained at 25 mT; the supersonic flame spraying process parameters are: oxygen flow rate 45 m³ / h. 3 / h, kerosene flow rate 22L / h, powder feeding rate 55g / min, spraying distance 300mm, spray gun moving speed 600mm / s; 5. Magnetic field-assisted low-temperature aging and setting: Place the workpiece in a 25mT constant magnetic field atmosphere and introduce nitrogen for protection; heat to 400℃ at a heating rate of 3-5℃ / min, hold at the temperature for 60min, and cool with the furnace after the holding period. 6. Natural aging at room temperature: After the workpiece cools to room temperature, it is left to stand for 24 hours to obtain the finished coating.

[0041] Performance testing showed that the coating obtained in this embodiment had an interfacial bonding strength of 72 MPa and a porosity of 0.98%. After 49 cycles of water quenching and thermal shock testing at 800℃, the coating failed, and the interlayer oxides within the coating disappeared. The high-temperature friction and wear rate at 800℃ was 1.15 × 10⁻⁶. -5 mm 3 / (N・m).

[0042] Example 3: In this example, a magnetic field-assisted in-situ nanocrystalline thermal spray coating was prepared using 45# steel as the substrate. The specific steps are as follows: 1. Substrate pretreatment: The 45# steel workpiece is ultrasonically degreased with acetone for 15 minutes, and then sandblasted with 80-mesh white corundum at a sandblasting pressure of 0.5MPa and a sandblasting angle of 75° to control the surface roughness Ra = 5.0μm. After blowing off the surface dust with clean compressed air, it is dried for later use. 2. Substrate magnetic field pre-polarization: The workpiece is placed in a steady magnetic field perpendicular to the surface of the substrate with a field strength of 35mT and pre-polarized for 15min. 3. Powder pretreatment: Prepare composite powder according to the following mass percentages: Cr3C2 35%, NiCrBSi nickel-based self-fluxing alloy powder 62%, La2O3 1.5%, ZrB2 1.5%, mix evenly and dry in an oven at 100℃ for 60 min to remove adsorbed moisture. 4. Synchronous magnetic field-assisted supersonic flame spraying: A magnetic field perpendicular to the substrate surface is applied throughout the spraying process, with the field strength maintained at 35 mT; the supersonic flame spraying process parameters are: oxygen flow rate 45 m³ / h. 3 / h, kerosene flow rate 22L / h, powder feeding rate 55g / min, spraying distance 300mm, spray gun moving speed 600mm / s; 5. Magnetic field-assisted low-temperature aging and setting: Place the workpiece in a 35mT constant magnetic field atmosphere and introduce nitrogen for protection; heat to 400℃ at a heating rate of 3-5℃ / min, hold at the temperature for 60min, and cool with the furnace after the holding period. 6. Natural aging at room temperature: After the workpiece cools to room temperature, it is left to stand for 24 hours to obtain the finished coating.

[0043] Performance testing showed that the coating obtained in this embodiment had an interfacial bonding strength of 78 MPa and a porosity of 0.6%. After 65 cycles of water quenching and thermal shock testing at 800℃, the coating failed, and the interlayer oxides within the coating disappeared. The high-temperature friction and wear rate at 800℃ was 6.36 × 10⁻⁶. -6 mm 3 / (N・m).

[0044] Example 4: In this example, a magnetic field-assisted in-situ nanocrystalline thermal spray coating was prepared using 45# steel as the substrate. The specific steps are as follows: 1. Substrate pretreatment: The 45# steel workpiece is ultrasonically degreased with acetone for 15 minutes, and then sandblasted with 80-mesh white corundum at a sandblasting pressure of 0.5MPa and a sandblasting angle of 75° to control the surface roughness Ra = 5.0μm. After blowing off the surface dust with clean compressed air, it is dried for later use. 2. Substrate magnetic field pre-polarization: The workpiece is placed in a steady magnetic field perpendicular to the surface of the substrate with a field strength of 35mT and pre-polarized for 15min. 3. Powder pretreatment: Prepare composite powder according to the following mass percentages: Cr3C2 36%, NiCrBSi nickel-based self-fluxing alloy powder 62%, La2O3 1%, ZrB2 1%. After mixing evenly, place it in an oven at 100℃ for 60 minutes to remove adsorbed moisture. 4. Synchronous magnetic field-assisted supersonic flame spraying: A magnetic field perpendicular to the substrate surface is applied throughout the spraying process, with the field strength maintained at 35 mT; the supersonic flame spraying process parameters are: oxygen flow rate 45 m³ / h. 3 / h, kerosene flow rate 22L / h, powder feeding rate 55g / min, spraying distance 300mm, spray gun moving speed 600mm / s; 5. Magnetic field-assisted low-temperature aging and setting: Place the workpiece in a 35mT constant magnetic field atmosphere and introduce nitrogen for protection; heat to 400℃ at a heating rate of 3-5℃ / min, hold at the temperature for 60min, and cool with the furnace after the holding period. 6. Natural aging at room temperature: After the workpiece cools to room temperature, it is left to stand for 24 hours to obtain the finished coating.

[0045] Performance testing showed that the coating obtained in this embodiment had an interfacial bonding strength of 79 MPa and a porosity of 0.54%. After 69 cycles of water quenching and thermal shock testing at 800℃, the coating failed, and the interlayer oxides within the coating disappeared. The high-temperature friction and wear rate at 800℃ was 6.68 × 10⁻⁶. -6 mm 3 / (N・m).

[0046] Example 5: In this example, a magnetic field-assisted in-situ nanocrystalline thermal spray coating was prepared using 45# steel as the substrate. The specific steps are as follows: 1. Substrate pretreatment: The 45# steel workpiece is ultrasonically degreased with acetone for 15 minutes, and then sandblasted with 80-mesh white corundum at a sandblasting pressure of 0.5MPa and a sandblasting angle of 75° to control the surface roughness Ra = 5.0μm. After blowing off the surface dust with clean compressed air, it is dried for later use. 2. Substrate magnetic field pre-polarization: The workpiece is placed in a steady magnetic field perpendicular to the surface of the substrate with a field strength of 35mT and pre-polarized for 15min. 3. Powder pretreatment: Prepare composite powder according to the following mass percentages: Cr3C2 34%, NiCrBSi nickel-based self-fluxing alloy powder 62%, La2O3 2%, ZrB2 2%, mix evenly and dry in an oven at 100℃ for 60 min to remove adsorbed moisture. 4. Synchronous magnetic field-assisted supersonic flame spraying: A magnetic field perpendicular to the substrate surface is applied throughout the spraying process, with the field strength maintained at 35 mT; the supersonic flame spraying process parameters are: oxygen flow rate 45 m³ / h. 3 / h, kerosene flow rate 22L / h, powder feeding rate 55g / min, spraying distance 300mm, spray gun moving speed 600mm / s; 5. Magnetic field-assisted low-temperature aging and setting: Place the workpiece in a 35mT constant magnetic field atmosphere and introduce nitrogen for protection; heat to 400℃ at a heating rate of 3-5℃ / min, hold at the temperature for 60min, and cool with the furnace after the holding period. 6. Natural aging at room temperature: After the workpiece cools to room temperature, it is left to stand for 24 hours to obtain the finished coating.

[0047] Performance testing showed that the coating obtained in this embodiment had an interfacial bonding strength of 74 MPa and a porosity of 0.79%. After 62 cycles of water-quenched thermal shock testing at 800℃, the coating failed, and the interlayer oxides within the coating disappeared. The high-temperature friction and wear rate at 800℃ was 6.19 × 10⁻⁶. -6 mm 3 / (N・m).

[0048] Comparative Example: This comparative example uses a conventional non-magnetic field-assisted supersonic flame spraying process to prepare a comparative coating, with 45# steel as the substrate. Details are as follows: The coating material consists of 62% NiCrBSi nickel-based self-fluxing alloy powder and 35% Cr3C2 powder, with 1.5% La2O3 and 1.5% ZrB2 additives. No magnetic field pre-polarization, magnetic field-assisted spraying, or magnetic field aging processes are included. The remaining pretreatment, basic spraying parameters, and post-treatment are consistent with conventional industrial processes.

[0049] Performance testing showed that the interfacial bonding strength of the coating prepared in this comparative example was 51 MPa; after 16 cycles of water quenching thermal shock testing at 800℃, the coating failed; and the high-temperature friction and wear rate at 800℃ was 2.12 × 10⁻⁶. -5 mm 3 / (N・m).

[0050] By comparing the above embodiments with the comparative examples, it can be seen that the present invention, through the three-stage magnetic field control throughout the entire process combined with rare earth-boride composite nucleation aid, can suppress the growth of coarse columnar crystals from the solidification mechanism level, generate diffusely distributed nanocrystals in situ, eliminate the weak bonding interface of traditional thermal spray coatings, and regulate the residual tensile stress into a uniform compressive stress field, ultimately achieving a significant improvement in coating bonding strength, thermal shock resistance, and high-temperature wear resistance.

[0051] It should be noted that, in this invention, although the specification describes the embodiments, not every embodiment contains only one independent technical solution. This way of describing the specification is only for clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A magnetic field-assisted in-situ nanocrystalline thermal spray coating, adhered to the surface of a metal substrate, comprising a Cr3C2 hard phase and a NiCrBSi nickel-based self-fluxing alloy binder phase, characterized in that: The coating has no lamellar weak bonding interface inside, and is composed of a micron-scale dense texture consisting of a micron-scale hard matrix phase and in-situ self-generated nanocrystals. The in-situ self-generated nanocrystals are dispersed at the grain boundaries and micro-interstic spaces of micron-sized particles; The coating has no through-holes or continuously expanding microcracks, and the overall internal stress is in a state of uniform residual compressive stress distribution.

2. The magnetic field-assisted in-situ nanocrystalline thermal spray coating according to claim 1, characterized in that, The size of the in-situ self-generated nanocrystals is 50–200 nm.

3. The magnetic field-assisted in-situ nanocrystalline thermal spray coating according to claim 1, characterized in that, The composite spraying powder used to prepare the coating, by mass percentage, consists of: Cr3C2 35%–45%, NiCrBSi nickel-based self-fluxing alloy powder 52%–62%, La2O3 1.0%–2.0%, and ZrB2 1.0%–2.0%.

4. A method for preparing a magnetic field-assisted in-situ nanocrystalline thermal spray coating as described in any one of claims 1-3, comprising substrate pretreatment, powder pretreatment, and supersonic flame spraying steps, characterized in that, Also includes: The substrate is pre-polarized by magnetic field before spraying; A constant magnetic field is continuously applied throughout the spraying process to assist deposition. After spraying, the coating is subjected to low-temperature aging and setting treatment in a stable magnetic field atmosphere; The powder used for spraying is a composite spraying powder containing Cr3C2, NiCrBSi nickel-based self-fluxing alloy powder, La2O3 and ZrB2.

5. The method for preparing a magnetic field-assisted in-situ nanocrystalline thermal spray coating according to claim 4, characterized in that, The magnetic field direction of the pre-polarization treatment is perpendicular to the substrate surface, the magnetic field strength is 15-35 mT, and the treatment time is 10-20 min. During the supersonic flame spraying process, the direction of the steady magnetic field is perpendicular to the surface of the substrate, and the magnetic field strength is maintained at 15-35 mT. The magnetic field strength of the low-temperature aging and shaping treatment is 15–35 mT.

6. The method for preparing a magnetic field-assisted in-situ nanocrystalline thermal spray coating according to claim 4, characterized in that, The substrate pretreatment includes a sandblasting roughening process: Using 80-100 mesh white corundum abrasive, the sandblasting pressure is controlled at 0.4-0.6 MPa, the sandblasting angle is controlled at 70°-80°, and the surface roughness Ra of the substrate after treatment is 4.0-6.0 μm.

7. The method for preparing a magnetic field-assisted in-situ nanocrystalline thermal spray coating according to claim 4, characterized in that, The process parameters for supersonic flame spraying include: Oxygen flow rate 45m 3 / h, kerosene flow rate 22L / h, powder feeding rate 55g / min, spraying distance 300mm, spray gun moving speed 600mm / s.

8. The method for preparing a magnetic field-assisted in-situ nanocrystalline thermal spray coating according to claim 4, characterized in that, The low-temperature aging and shaping treatment was carried out under inert nitrogen protection, with the heating rate controlled at 3-5℃ / min. After heating to 400℃, the temperature was held at a constant temperature for 60 minutes, and then cooled with the furnace after the holding period.

9. The method for preparing a magnetic field-assisted in-situ nanocrystalline thermal spray coating according to claim 8, characterized in that, After the low-temperature aging and shaping treatment is completed, the workpiece cooled to room temperature is left to stand for 24 hours for natural aging at room temperature to obtain the final coating product.